Penerapan Metode Takrir dalam Menghafal Al-Qur’an di Sekolah Dasar Balitaku Khatam Quran Super Tanjung Sari Medan - Januari Simarmata; Hadi Saputra Panggabean; Muhammad Yunan Harahap (Pedagogika: Jurnal Ilmu-Ilmu Kependidikan, 2026)
This study examines the implementation of the Takrir method in Qur’anic memorization among elementary school students at Balitaku Khatam Quran Super Tanjung Sari Medan and evaluates its effectiveness in improving students’ memorization consistency and retention. The research addresses how repetitive memorization guided by teachers contributes to students’ ability to memorize the Qur’an systematically and effectively at the elementary education level. This study employed a qualitative case study approach, with data collected through observation, interviews, and documentation. The findings reveal that the consistent application of the Takrir method significantly improves students’ memorization skills, strengthens concentration, and cultivates disciplined learning habits during the memorization process. The study also found that intensive repetition combined with teacher guidance creates positive interactions between teachers and students, making the learning environment more engaging and supportive. This study concludes that the Takrir method is an effective instructional strategy for Qur’anic memorization at the elementary school level because it supports gradual memorization, strengthens long-term retention, and enhances students’ learning motivation and discipline.